Analysis of the hypothalamic oxytocin system and oxytocin receptor-expressing astrocytes in a mouse model of Prader-Willi syndrome - Althammer, Ferdinand; Wimmer, Moritz Claudius; Krabichler, Quirin; Schimmer, Stephanie; Schimmer, Jonas; Fröhlich, Henning; Dötsch, Laura; Gruber, Tim; Wunsch, Selina; Schubert, Tim; Kirchner, Matthew K.; Stern, Javier E.; et al. (Journal of neuroendocrinology, 2022)
Prader-Willi syndrome (PWS) is a neurodevelopmental disorder characterized by hyperphagia, obesity, developmental delay and intellectual disability. Studies suggest dysfunctional signaling of the neuropeptide oxytocin as one of the key mechanisms in PWS, and administration of oxytocin via intranasal or systemic routes yielded promising results in both humans and mouse models. However, a detailed assessment of the oxytocin system in mouse models of PWS such as the Magel2-deficient Magel2tm1.Stw mouse, is lacking. In the present study, we performed an automated counting of oxytocin cells in the entire paraventricular nucleus of the hypothalamus of Magel2tm1.Stw and wild-type control mice and found a significant reduction in the caudal part, which represents the parvocellular subdivision. In addition, based on the recent discovery that some astrocytes express the oxytocin receptor (OTR), we performed detailed analysis of astrocyte numbers and morphology in various brain regions, and assessed expression levels of the astrocyte marker glial fibrillary acidic protein, which was significantly decreased in the hypothalamus, but not other brain regions in Magel2tm1.Stw mice. Finally, we analyzed the number of OTR-expressing astrocytes in various brain regions and found a significant reduction in the nucleus accumbens of Magel2tm1.Stw mice, as well as a sex-specific difference in the lateral septum. This study suggests a role for caudal paraventricular nucleus oxytocin neurons as well as OTR-expressing astrocytes in a mouse model of PWS, provides novel information about sex-specific expression of astrocytic OTRs, and presents several new brain regions containing OTR-expressing astrocytes in the mouse brain.
Erstmals online veröffentlicht: 14. November 2022
Gesehen am 27.08.2024